2011
DOI: 10.1172/jci44943
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB–inducing kinase plays an essential T cell–intrinsic role in graft-versus-host disease and lethal autoimmunity in mice

Abstract: NF-κB-inducing kinase (NIK) is an essential upstream kinase in noncanonical NF-κB signaling. NIK-dependent NF-κB activation downstream of several TNF receptor family members mediates lymphoid organ development and B cell homeostasis. Peripheral T cell populations are normal in the absence of NIK, but the role of NIK during in vivo T cell responses to antigen has been obscured by other developmental defects in NIKdeficient mice. Here, we have identified a T cell-intrinsic requirement for NIK in graft-versus-hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 57 publications
(77 reference statements)
2
81
0
Order By: Relevance
“…2C), suggesting that NIK mutation in hematopoietic cells also plays a role in Treg production. This finding supports a T cell-intrinsic role of NIK (15)(16)(17)(18)(19)(20). However, one study has suggested that the phenotypes of T cells from aly mice are attributable to abnormal function of DCs lacking normal NIK (21).…”
Section: Maturation Process Of Conventional Ab T Cells Is Also Contromentioning
confidence: 52%
See 2 more Smart Citations
“…2C), suggesting that NIK mutation in hematopoietic cells also plays a role in Treg production. This finding supports a T cell-intrinsic role of NIK (15)(16)(17)(18)(19)(20). However, one study has suggested that the phenotypes of T cells from aly mice are attributable to abnormal function of DCs lacking normal NIK (21).…”
Section: Maturation Process Of Conventional Ab T Cells Is Also Contromentioning
confidence: 52%
“…Taken together, these results suggest that impaired Treg production in aly mice is at least partly stroma dependent and associated with the defect in the production of mature CD80 high mTECs. Although the data presented above suggested that impaired de novo production of Tregs in aly mice is thymic stroma dependent, we and others previously demonstrated that NIK mutation also affects T cell reactivity in a cell-autonomous manner (15)(16)(17)(18)(19)(20) that can affect Treg lineage commitment (4). Therefore, we examined whether impaired de novo production of Tregs also depends on NIK in hematopoietic cells by generating reciprocal BM chimeras.…”
Section: Nik Mutation Affects the De Novo Production Of Tregs In The mentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, we sought to investigate other pathways downstream of 4-1BB that could affect proliferation and cytokine production. Recently it has been reported that NIK, an activator of the alternative NF-B pathway, is absolutely required for costimulation through the TNF receptor family member OX40 in graft-versus-host disease (43). A previous report showed that overexpresson of 4-1BB in 293 cells leads to the appearance of p52 (31).…”
Section: -1bb Activates the Alternative Nf-b Pathway In T Cellsit Wamentioning
confidence: 99%
“…NIK expressed by CD4 + T cells plays an essential role in graft-versus-host disease, and NIK signaling via OX40 is required for the lethal autoimmunity (Murray et al 2011). NIK is also important for generation and maintenance of CD4 + and CD8 + memory T cells in response to LCMV infection (Rowe et al 2013).…”
Section: Traf3 In Signalmentioning
confidence: 99%